Cardiac progression of systemic light chain amyloidosis - Chango Azanza, Diego Xavier (2022)
Systemic light chain amyloidosis is a disease characterized by the accumulation of amyloid protein in multiple organs and systems. We present the case of a 52-year-old male patient with a diagnosis of systemic light chain amyloidosis associated with cardiac and renal involvement. A renal biopsy showed the presence of renal amyloidosis associated with proteinuria, and the patient was referred for cardiovascular evaluation. The baseline electrocardiogram showed micro voltage in frontal leads that were discordant with the left ventricular hypertrophy evidenced in the transthoracic echocardiogram (TTE). Cardiac magnetic resonance imaging (CMR) confirmed the presence of cardiac amyloid infiltration with a pattern of extensive ventricular late-gadolinium enhancement. Despite being referred and receiving specific systemic chemotherapy treatment, the evolution was not favorable after four months of follow-up with worsening cardiac infiltration, increasing values of biomarkers, and progression of dyspnea. The TTE was useful in revealing the unfavorable evolution and worsening of diastolic function parameters and increased wall thickness in the context of infiltration. The electrocardiogram and echocardiogram were easily accessible tools that allowed the monitoring of the response to treatment.